Analisis Pecahnya Windlass Hydraulic Motor di Kapal MV. Lumoso Aman - Fendy Aula Rizalul Ilmi; Eka Darmana; Fajar Pujiyanto (JURNAL BARTEK, 2025)
During the author's observation on the MV. Lumoso Aman, a ship in Sulawesi waters, more precisely in Bahodopi in 2023, there was damage to the hydraulic motor windlass when raising anchor in the middle of the sea and the ship's maneuvering process was delayed. This study aims to analyze the main causes of the rupture of the windlass hydraulic motor, analyze the impact on hydraulic motor damage, and prevention and maintenance methods to maintain the efficiency of ship maneuvering and loading and unloading. The research method used is a qualitative case study by conducting direct research on the MV. Lumoso Aman. The method for data collection uses 3 techniques, namely by conducting observation, documentation, and interviews. This observation was carried out on the MV. Lumoso Aman. This documentation takes photos of activities related to the incident. Interviews were conducted after the incident by taking information from electrical and machinist II. The data analysis method uses a qualitative descriptive approach by concluding various opinions, data and literature. The results of the study showed that damage to the hydraulic motor hampered ship maneuvers and loading and unloading at the port. When the hydraulic system is clogged, hydraulic oil cannot flow into the system and affects the hydraulic motor and other components. Blocked oil pressure can cause excessive heat in the hydraulic motor and at worst can be damaged. To overcome this problem, preventive measures are needed such as regular maintenance, implementation of a monitoring system on the windlass components and cleaning the hydraulic filter.